Genetic Structure of a Worldwide Germplasm Collection of Prunus armeniaca L. Reveals Three Major Diffusion Routes for Varieties Coming From the Species’ Center of Origin - Bourguiba, Hedia; Scotti, Ivan; Sauvage, Christopher; Zhebentyayeva, Tetyana; Ledbetter, Craig; Krška, Boris; Remay, Arnaud; D’Onofrio, Claudio; Iketani, Hiroyuki; Christen, Danilo; Krichen, Lamia; Trifi-Farah, Neila; et al. (Frontiers in Plant Science, 2020)
The characterization of the largest worldwide representative data set of apricot (Prunus armeniaca L.) germplasm was performed using molecular markers. Genetic diversity and structure of the cultivated apricot genetic resources were analysed to decipher the history of diffusion of this species around the world. A common set of 25 microsatellite markers was used for genotyping a total of 890 apricot accessions in different collections from the centre of origin to the more recent regions of apricot culture. Using a Bayesian model-based clustering approach, the apricot genotypes can be structured into five different genetic clusters (FST = 0.174), correlated with the geographical regions of origin of the accessions. Accessions from China and Central Asia were clustered together and exhibited the highest levels of diversity, confirming an origin in this region. A loss of genetic diversity was observed from the centre of origin to both western and eastern zones of recent apricot culture. Altogether, our results revealed that apricot spread from China and Central Asia, defined as the centre of origin, following three major diffusion routes with a decreasing gradient of genetic variation in each geographical groups. The identification of specific alleles outside the centre of origin confirmed the existence of different secondary apricot diversification centres. The present work provides more understanding of the worldwide history of apricot species diffusion as well as the field of conservation of the available genetic resources. Data have been used to define an apricot core collection based on molecular marker diversity which will be useful for further identification of genomic regions associated with commercially important horticultural traits through genome-wide association studies to sustain apricot breeding programs.